Progress and Challenges of Implementing Decentralized HIV Testing For Prevention of Mother-to-Child Transmission of HIV - Myanmar - San Hone, PhD; Li Li, PhD; Sung-Jae Lee, PhD; W. Scott Comulada, PhD; Roger Detels, MD, MS (Global Health and Education Projects, Inc., 2019)
Background: Myanmar has adopted point-of-care (POC) HIV testing for its prevention of mother-to-child transmission of HIV program, and was initiated in 84 townships in 2013. This study assessed the progress of HIV testing uptake from 2012, one year prior to POC testing, to 2015, and the challenges faced by service providers during the rapid rollout of this testing strategy. Methods: This serial cross-sectional study included 23 townships randomly selected from the 84 townships. An open-question survey was used to collect information on the challenges faced by service providers. A random effects logistic model was used for assessing the progress of HIV testing uptake among urban and rural health center groups. Results: HIV testing uptake for antenatal care (ANC) attendees increased from 60% to 90% for rural and from 70% to 90% for urban attendees. The proportion of ANC attendees who were tested at their first visit increased from 70% to 80% for rural and from 70% to 90% for urban attendees. In addition, the proportion receiving same-day test results increased from less than 10% to 90% for both groups. Major challenges faced during the initial rollout included low health awareness among pregnant women, fear of stigma and discrimination, long travel times and costs, and increased workloads of providers in rural settings. Conclusions and Global Health Implications: The program should consider recruiting local volunteers to help reduce the workloads of service providers. Professional education based on need and continued mentoring and quality control schemes for HIV testing need to be in place. This decentralized strategy would be applicable to other resource-limited countries. Key words:  • HIV/AIDS • Pregnant Women • Point-of-Care (POC) HIV Testing • Antenatal Care (ANC) • Prevention of Mother-to-Child Transmission of HIV (PMCT) • Service Cascade • Stigma and Discrimination   Copyright © 2019 Hone et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.